Improvement of the mass rearing of larvae of the neotropical lacewing Chrysoperla externa through the incorporation of a new semiliquid artificial diet - Haramboure, Marina (2016)
Two new semiliquid artificial diets (A and B), the aphid Rhopalosiphum padi L. (Hemiptera: Aphididae) and combinations of these were evaluated to improve the rearing of the Neotropical lacewing predator Chrysoperla externa (Neuroptera: Chrysopidae). Additionally, a nutritional analysis of the aforementioned diets was conducted. The developmental time, pupal weight, preoviposition period, fecundity, and fertility were used to evaluate the impact (i.e., potential benefit) of these artificial diets on the predator. We recorded the shortest development time in the treatment group that was given diet A + prey or prey alone ad libitum. Pupal weight was significantly higher with diet A + prey. No difference was found in the female preoviposition period between the five different diets. Fecundity was higher with diet A + prey or prey ad libitum, while fertility on the first day was higher with diet A + prey, cumulative fertility was optimal with diet A and B as food. In conclusion, diet A proved to have the optimal nutritional properties (proteins and carbohydrates) to improve lacewing rearing when used as a nutritional supplement. Furthermore, use of this diet allows a reduction in the use of prey for rearing, and is suitable to be used for mass-rearing programs.